Діагностика ймовірності банкрутства підприємства та шляхи його стабілізації - Іщенко, Н. А.; Íshchenko, N. (ЦНТУ, 2017)
У статті висвітлено методичні підходи до діагностики ймовірності банкрутства підприємства. Проаналізовано ймовірність банкрутства підприємства за допомогою моделей прогнозування банкрутства. Визначено обмеження для використання на українських підприємствах моделей прогнозування банкрутства зарубіжних вчених. Обгрунтовано напрями використання результатів прогнозування при розробці стратегічних механізмів фінансової стабілізації. The article’s aim is to elucidate the methodological approaches to the diagnosis of probability of the enterprise bankruptcy and ways to stabilize its financial condition. The study used general scientific and special methods (comparative, economic and statistical). It was done the diagnosis of probability of the enterprise bankruptcy with the help of five-factor E. Altman, J. Bevere, Springate’s model, generalized model, Sayfulina-Kadykova’s model, Irkutsk model and O. Tereshchenko’s model. We have found restrictions for use by Ukrainian enterprises bankruptcy prediction models of foreign scientists. There were proposed the national adapted economy methods taking into consideration foreign bankruptcy prediction models. The results of the evaluation of the bankruptcy probability demonstrate financial stability of the company and the law probability of the bankruptcy. The research results ascertain that using the strategic mechanism of the financial stabilization is expedient. Strategic mechanism of the financial stabilization is a system of the measures that based on using the financial support models of the rapid economic growth of the enterprise, namely an effective pricing policy, tax policy; dividend policy.
The diagnosis of probatility of the enterprise bankruptcy and ways to stabilize it
Keywords: банкрутство; діагностика ймовірності банкрутства; моделі прогнозування банкрутства; фінансова стабілізація; bankruptcy; diagnosis; probability of bankruptcy; bankruptcy prediction model; financial stabilization